Association between social support and adherence to anti-retroviral treatment in people living with HIV - Rafael da Silva Oliveira; Marcelo Ribeiro Primeira; Wendel Mombaque dos Santos; Cristiane Cardoso de Paula; Stela Maris de Mello Padoin (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To investigate the association between social support, adherence to HIV anti-retroviral therapy, and clinical and sociodemographic factors. Method: A cross-sectional study conducted from July 2016 to August 2018 in a specialized outpatient clinic in southern Brazil. Individual interviews were conducted for the application of the following instruments: Questionnaire for the Evaluation of Adherence to Anti-retroviral Treatment (CEAT-HIV) and Social Support Scale for People Living with HIV/AIDS. The Spearman bivariate correlation test was used for analysis purposes. Results: Among the 168 participants, the mean social support score was 3.53 points (SD = 0.66), and 64.9% (n = 109) of the respondents had insufficient adherence. There was a significant association (p < 0.05) between emotional social support and the following adherence domains: antecedents of non-adherence behaviors and doctor-patient communication. Conclusions: Social support is associated with antecedents of non-adherence behaviors and doctor-patient communication.